Análisis de la Variabilidad de la Frecuencia Cardiaca durante Entrenamiento Físico de Distinta Intensidad a través de Índices de la Gráfica de Poincaré - Martínez Hernández, Veronica Janeth; Dorantes Méndez, Guadalupe; Mejía Rodríguez, Aldo Rodrigo (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Exercise induces parasympathetic withdrawal and sympathetic activation. Heart rate variability (HRV) is a noninvasive tool for the assessment of cardiac autonomic function. Physical training can improve cardiovascular health through an increase in HRV. In this study, two physical trainings were conducted, one with moderate intensity (MT) and the second one with higher intensity (IT), for 10 weeks. A test protocol which consisted of 3 maneuvers: control, exercise, and recovery was performed each week of training to follow up the HRV changes in 18 sedentary volunteers aged 20.3±2 years. The RR intervals were analyzed by indexes of traditional Poincaré plot (SPP) and segmented Poincaré plot (SEPP). The results showed an increase in column 7 probabilities in week 10 with respect to week 4 during control stage for both trainings. Regarding, trainings differences, row 9 probability decreases in MT training suggesting a higher cardiac vagal activity in this training.